1999
DOI: 10.1002/(sici)1097-0142(19991101)86:9<1768::aid-cncr19>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in the quality of life of breast carcinoma patients after treatment

Abstract: Results from this analysis suggest that younger women with breast carcinoma should be considered to be at high risk for QOL disruption and significant clinical distress. Targeted interventions for this cohort are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
3
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 0 publications
3
54
3
1
Order By: Relevance
“…In the present study, there was no significant difference between QOL scores before and after POC, and the difference in Physical symptoms and pain, and Dress, sexual aspect, other subscale category scores seen before POC was not apparent after POC, probably reflecting tumour shrinkage in patients who initially experienced pain and skin ulceration, with improved QOL due to the disappearance of breast cancer symptoms. One study found no significant difference in physical symptoms or functional aspects between older and young women, although younger patients experienced a significant decrease in QOL; however, the present study found no influence related to age.…”
Section: Discussioncontrasting
confidence: 88%
“…In the present study, there was no significant difference between QOL scores before and after POC, and the difference in Physical symptoms and pain, and Dress, sexual aspect, other subscale category scores seen before POC was not apparent after POC, probably reflecting tumour shrinkage in patients who initially experienced pain and skin ulceration, with improved QOL due to the disappearance of breast cancer symptoms. One study found no significant difference in physical symptoms or functional aspects between older and young women, although younger patients experienced a significant decrease in QOL; however, the present study found no influence related to age.…”
Section: Discussioncontrasting
confidence: 88%
“…Quality of life is associated with many variables such as age, cancer diagnosis and fear of recurrence 7−9,11,12,19,21,33 . In this study the three treatment groups were statistically different in terms of age both at the time of diagnosis and at the time of interview when the mastectomy group was the eldest, followed by the breast conservation group, and then the breast reconstruction group.…”
Section: Discussionmentioning
confidence: 79%
“…This may play a factor in quality of life assessment as Wenzel et al. 33 found in his study of 304 breast cancer patients who were compared on a quality of life assessment based on age above and below 50 years. The younger patients had significantly worse quality of life, especially in the domain of emotional well being and breast cancer related specific concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings must be interpreted with caution given the wide 95% CI reflecting our small sample size. We should note that current reports from clinical practice are quite different from clinical trials, with up to 30% of women with breast cancer stopping treatment early in practice settings (20,32). Second, our study population was mostly white and young, with excellent performance status.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, we were not able to explore the contribution of psychosocial factors previously found to affect a cancer patient’s ability to finish treatment protocols (16–20). In a study of patients who had already dropped out of treatment, researchers reported that patients with depressed mood or a poorer adjustment to their diagnosis were less likely to finish treatment (17).…”
Section: Discussionmentioning
confidence: 99%